A water quality model applied for the rivers into the Qinhuangdao coastal water in the Bohai Sea, China - 顾杰 胡成飞 匡翠萍 Olaf KOLDITZ 邵亥冰 张甲波 刘会欣 (Journal of hydrodynamics. Series B, 2016)
The water quality of all rivers into the Qinhuangdao coastal water was below the grade V in 2013. In this study, an inte- grated MIKE 1 l water quality model is applied to deal with the water environment in the rivers into the Qinhuangdao coastal water. The model is first calibrated with the field measured chemical oxygen demand （COD） concentrations. Then the transport of the COD in the rivers into the Qinhuangdao coastal water is computed based on the model in the water environmental monitoring process. Numerical results show that the COD concentration decreases dramatically in the estuaries, from which we can determine the positions of long-term monitoring stations to monitor the river pollutions into the coastal water. Furthermore, different scenarios about the inputs of the point sources and the non-point sources are simulated to discuss the model application in the water enviro- nmental control, and simplified formula are derived for assessing the water quality and the environmental management of rivers.